Options for the Treatment of Gemcitabine-Resistant Advanced Pancreatic Cancer: Are We There Yet? - Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Yale Cancer Center. New Haven, CT, USA.